Evaluation of the Use of Anticoagulotherapy in Cancer Patients in Palliative Care Residence - Stefano Polesello; Sebastian Georgescu; Tal?a Malag?n; Sylvie Bouchard (Palliative Medicine Reports, 2023)
Background: Several patients admitted to palliative care residences are on anticoagulotherapy (AC). Given the risks of venous thromboembolism (VTE) and bleeding, the decision to continue or stop AC on admission remains clinically challenging. Objectives: To determine the prevalence of AC use and incidence of suspected VTE and bleeding events in palliative care patients. Methods: Retrospective cohort study including all deceased patients at a Canadian palliative care residence over two years. Results: Among the 453 patients' charts reviewed (369 with cancer), 183 (40%) were on AC at admission or <30 days earlier. Only 64 (35%) continued AC, with 78% discontinuing it during their stay. Demographic parameters were similar in the AC and non-AC groups. The incidence of suspected VTE was lower in patients pursuing AC post-admission than in those who stopped: (4.6% vs. 6.7%) and, conversely, the incidence of bleeding was higher in patients on AC: (10.8% vs. 7.6%), though these differences were not statistically significant. The risk of death in cancer patients within 72 hours of suspected VTE or bleeding event was 80% and 30%, respectively. Patients on AC had a 33% reduced risk of VTE but a 44% increased risk of bleeding. Conclusion: This study provides information on the AC use in palliative care patients. In term of survivorship, it suggests a possible advantage to continue AC to prevent a symptomatic or distressing death. Given the low incidence of events, larger powered studies will be necessary to further characterize the risks/benefits of pursuing AC in patients in palliative care residences.